A Recent Human Immunodeficiency Virus Outbreak Among People Who Inject Drugs in Munich, Germany, Is Associated With Consumption of Synthetic Cathinones. (27th May 2020) - Hanke, Kirsten; Fiedler, Stefan; Grumann, Christina; Ratmann, Oliver; Hauser, Andrea; Klink, Patrycja; Meixenberger, Karolin; Altmann, Britta; Zimmermann, Ruth; Marcus, Ulrich; Bremer, Viviane; Auwärter, Volker; et al.
Abstract: Background: Needle and syringe sharing among people who inject drugs (PWID) can result in a rapid regional spread of a human immunodeficiency virus (HIV) variant. Such outbreaks have been identified recently in several countries and have raised public health attention because of an association with new psychoactive substances (NPS). Methods: Dried serum spots from approximately 60% of newly diagnosed HIV cases in Germany in 2013–2018 were received together with statutory notification data. Samples were sequenced in the pol- region, genotyped, and viral phylogenies were analyzed. For selected samples, the hepatitis C virus (HCV) status and the presence of NPS were determined. Results: An outbreak of closely related 27 subtype C infections with a core of 11 cases with almost identical sequences was identified using phylogenetic analyses. The first case of the outbreak was diagnosed in 2015, and the last one was in 2018. With exception of 3 infections, all were reported from Munich, the capital of the federal state of Bavaria. Of 26 analyzed outbreak members, 24 (92.3%) had a resolved or viremic HCV coinfection. In 8 of 18 (44%) cases, α-pyrrolidinopentiothiophenone and/or the related substance α-pyrrolidinoheptiophenone was identified. Conclusions: Despite harm reduction services in place, HIV outbreaks of considerable size can occur in PWID. The establishment of a real-time molecular surveillance is advised to rapidly identify outbreaks and target prevention measures. Abstract : We identify and analyze an HIV-1 outbreak in Munich, Bavaria among PWID. The cases are infections with a highly related subtype C virus. We find an association with consumption of synthetic cathinones and a very high rate of HCV coinfections.